The viper [large type] - Meltzer, Brad (Meltzer, Brad. Zig & Nola novel, 2026)
This novel follows the investigation into the murder of Andrew Fechmeier, a man who spent much of his life concealing a valuable secret. After his death, attention turns to an object hidden among his personal effects, drawing the interest of a determined killer. The case is taken up by an unconventional investigator whose personal history becomes increasingly connected to the crime. As the inquiry expands, long-buried family secrets, a decades-old murder, and conflicting accounts of the past come to light. The narrative explores themes of secrecy, loss, and the lasting impact of unresolved crimes.